2016
DOI: 10.1016/j.jmb.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a TCR-Mimic Antibody with Target Predicts Pharmacogenetics

Abstract: Antibody therapies currently target only extracellular antigens. A strategy to recognize intracellular antigens is to target peptides presented by immune HLA receptors. ESK1 is a human, T-cell receptor (TCR)-mimic antibody that binds with sub-nanomolar affinity to the RMF peptide from the intracellular oncoprotein Wilms Tumor 1 (WT1) in complex with HLA-A*02:01. ESK1 is therapeutically effective in mouse models of WT1+ human cancers. TCR-based therapies have been presumed to be restricted to one HLA subtype. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 53 publications
4
72
0
Order By: Relevance
“…The binding orientations of both mother clones were predicted to be diagonal across the peptide binding groove, but skewed towards the C-terminus of the peptide and the MHC α-chain when compared to crystal structures of TCRs with the same specificity (20). This agrees with results from studies showing that TCR-like antibodies generally bind diagonally, but can have more diverse orientations than TCRs (33)(34)(35)(36). Furthermore, it illustrates that other orientations for specific recognition of pMHC are possible than what is typically seen with naturally occuring TCRs, which may be restricted by co-receptor engagement and germline-imprinted MHC recognition motifs (37).…”
Section: Discussionsupporting
confidence: 88%
“…The binding orientations of both mother clones were predicted to be diagonal across the peptide binding groove, but skewed towards the C-terminus of the peptide and the MHC α-chain when compared to crystal structures of TCRs with the same specificity (20). This agrees with results from studies showing that TCR-like antibodies generally bind diagonally, but can have more diverse orientations than TCRs (33)(34)(35)(36). Furthermore, it illustrates that other orientations for specific recognition of pMHC are possible than what is typically seen with naturally occuring TCRs, which may be restricted by co-receptor engagement and germline-imprinted MHC recognition motifs (37).…”
Section: Discussionsupporting
confidence: 88%
“…Given that the antibody that binds to WT1/HLA-A2, called ESK1, also bound to peptides that shared the same N-terminal residues as the WT1 peptide (22), the PIGQ (RMFPGEVAL) peptide was tested for activity against the D13.1.1 TCR. Tetramers of the PIGQ peptide/HLA-A2 did not bind to the D13.1.1 TCR (data not shown), nor did the PIGQ peptide stimulate CD8 T cells that expressed the D13.1.1 TCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This antibody was tested for activity and toxicity in mice as a soluble Fc containing antibody, as a bi-specific molecule, and a CAR (1921). However, recent crystallographic studies showed that the ESK1 antibody docked over the N-terminus of the WT1 peptide, with atomic interactions limited to the first four peptide residues, thus explaining why ESK1 cross-reacted with other human peptides that shared these residues such as the peptide PIGQ (22). Since the ESK1 antibody lacks specificity for WT1 peptide, it is unlikely to be applied in more sensitive therapeutic approaches, such as adoptive T cell therapies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the therapeutic TCRm ESK1 binds to a composite antigen composed of HLA-A*02:01 amino acids in addition to three to five N-terminal residues of a WT1-derived peptide 9-mer. [10,16] Substitutions of the C-terminal amino acids of the target peptide still allows binding of the ESK1 TCRm. In addition, another TCRm (named 8F4) against the tumor-associated antigen PR1 has been shown to depend heavily on one residue of the PR1-peptide,[17] whereas a TCRm to the cancer-testis antigen PRAME[31] was shown to bind to the C-terminal end of the peptide sequence.…”
Section: Choosing the Right Antigenmentioning
confidence: 99%
“…Furthermore, HLA restriction selects small subsets of amino acid sequences for presentation, which means that an individual TCRm may work only for a subset of patients with particular HLA types. [10] Lastly, because the epitope consists of a linear peptide sequence within an MHC molecule (pMHC), there is also the possibility of cross-reactivity with other linear sequences that are homologous to the chosen epitope and may be presented on nontarget cells.…”
Section: Introductionmentioning
confidence: 99%